2019
DOI: 10.3390/nu11051084
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Availability and Physical Performance: Physiological Overview and Practical Recommendations

Abstract: Strong evidence during the last few decades has highlighted the importance of nutrition for sport performance, the role of carbohydrates (CHO) being of special interest. Glycogen is currently not only considered an energy substrate but also a regulator of the signaling pathways that regulate exercise-induced adaptations. Thus, low or high CHO availabilities can result in both beneficial or negative results depending on the purpose. On the one hand, the depletion of glycogen levels is a limiting factor of perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 84 publications
0
49
1
7
Order By: Relevance
“…The inclusion of sports drinks is essential to restore the sailor's hydroelectrolytic balance [65] and, thus, to alleviate one of the most frequent problems during sailing competitions, i.e., dehydration, and the consequent deterioration of performance and health of the sailor [16][17][18]43]. In addition, these drinks should include carbohydrates, which, added to their electrolytes, prevent the deterioration of endurance, strength, blood volume, and cognitive function in competitions of this duration [43,66]. The inclusion of sports foods such as bars or liquid meals can help the maintenance and replenishment of muscle glycogen, essential for maintaining performance and important in the light sail that includes multiple competition sessions on the same day or on successive days [43,65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of sports drinks is essential to restore the sailor's hydroelectrolytic balance [65] and, thus, to alleviate one of the most frequent problems during sailing competitions, i.e., dehydration, and the consequent deterioration of performance and health of the sailor [16][17][18]43]. In addition, these drinks should include carbohydrates, which, added to their electrolytes, prevent the deterioration of endurance, strength, blood volume, and cognitive function in competitions of this duration [43,66]. The inclusion of sports foods such as bars or liquid meals can help the maintenance and replenishment of muscle glycogen, essential for maintaining performance and important in the light sail that includes multiple competition sessions on the same day or on successive days [43,65].…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of sports foods such as bars or liquid meals can help the maintenance and replenishment of muscle glycogen, essential for maintaining performance and important in the light sail that includes multiple competition sessions on the same day or on successive days [43,65]. Due to the long duration of some of these competitions (sometimes longer than 5 h), protein and carbohydrate co-management is necessary to avoid prolonged periods of muscle protein degradation, especially when the competition lasts several successive days, helping in turn to reduce the muscle damage produced and to improve post-exercise recovery [43,65,66].…”
Section: Discussionmentioning
confidence: 99%
“…Formulated foods and sports foods, products which provide energy and nutrients in a more convenient form than normal foods for general nutrition support or for targeted use concerning exercise (sports drinks, sports gels or sports bars) [ 19 ], are some of the DS most consumed by athletes of different ages, sex, levels or sports [ 18 , 19 , 24 , 26 , 27 ], including rugby [ 33 , 34 ]. Sports drinks can be a good source of simultaneous delivery of fluid with carbohydrate during exercise, as well as post-exercise rehydration and refuelling [ 70 ]. On the other hand, sports bars can be useful as a carbohydrate source during exercise and post-exercise recovery, providing carbohydrate, protein and micronutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the limited results published in the literature, it has been found that an intake of complex carbohydrates during exercise-instead of consuming only glucose-or the optimal combination of glucose and fructose can prevent the occurrence of this problem. A sufficient amount of carbohydrates should be ingested to ensure the recovery of glycogen stores; this may vary between 5 and 12 g/kg body weight/day depending on the athlete and the physical activity performed [5,58]. If this is combined with a reduced dietary intake of fermentable oligosaccharides, disaccharides, and monosaccharides, the incidence of GI problems is lower [59].…”
Section: Gastrointestinal (Gi) Problems During Physical Exercisementioning
confidence: 99%